Quantile analysis of the effect of non-mandatory cash crop production on poverty among smallholder farmers - Placide Uwimana; Gideon A. Obare; Oscar Ayuya Ingasia (Economies, 2025)
Tea and coffee as traditional cash crops have been produced in Rwanda for more than six and ten decades respectively. However, new cash crops are being produced and exported, although their role in increased income and poverty reduction over traditional ones is not well understood; hence the analysis of drivers of both traditional and non-mandatory cash crop production among smallholder farmers is imperative. The study applied an experimental research design, and two strata composed of non-mandatory cash crops and traditional crop growers were used to obtain a simple random sample of 400 smallholder farmers. The study analysed the effect of cash crop production on multidimensional poverty among farmers in the Rulindo District using a quantile treatment effect. Although the poorest category of adopters places a high opportunity cost in allocating more time to off-farm activities, the poorest households that are female-headed are likely to increase multidimensional poverty once they adopt non-mandatory cash crops. Similarly, farm size does not help the poorest households to reduce poverty. Poorest households could be considered while introducing new non-mandatory cash crops because they do not help them reduce non-pecuniary poverty. Tea, coffee and food crops should be helpful among the poorest smallholder farmers.
Keywords: 330; non-mandatory cash crops; non-pecuniary poverty; multidimensional poverty index; small-scale cash crop farming; quantile treatment effect